To rewrite the expression \((x - 2)(8x + 6)\) using the distributive property, also known as the FOIL method for binomials, you will multiply each term in the first binomial by each term in the second binomial.
-
First: Multiply the first terms:
\[
x \cdot 8x = 8x^2
\]
-
Outer: Multiply the outer terms:
\[
x \cdot 6 = 6x
\]
-
Inner: Multiply the inner terms:
\[
-2 \cdot 8x = -16x
\]
-
Last: Multiply the last terms:
\[
-2 \cdot 6 = -12
\]
Now combine all of these results together:
\[
8x^2 + 6x - 16x - 12
\]
Next, combine the like terms \(6x\) and \(-16x\):
\[
8x^2 + (6x - 16x) - 12 = 8x^2 - 10x - 12
\]
Thus, the expression \((x - 2)(8x + 6)\) rewritten is:
\[
\boxed{8x^2 - 10x - 12}
\]